Defect engineering in nanozymes. (January 2022) - Wu, Yu; Xu, Weiqing; Jiao, Lei; Tang, Yinjun; Chen, Yifeng; Gu, Wenling; Zhu, Chengzhou
Graphical abstract: Abstract: Due to the high stability, various synthesis strategies, low cost, and tunable performance, nanozymes have gained much attention as the replacement of natural enzymes. To widen the application, highly active, specific, and robust nanozymes are in need. Recently, defects in nanomaterials have been verified to play a significant role in enhancing catalytic performances. Therefore, the marriage between defect engineering and nanozymes is expected to spark new possibilities. In this review, defect engineering strategies in nanozymes are summarized and the close relationships between defects and nanozyme properties are highlighted. It is anticipated that defect engineering will bring new opportunities to the evolving field of nanozymes.